2018
DOI: 10.1523/jneurosci.0635-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Activity in the Ventral Medial Prefrontal Cortex Is Necessary for the Therapeutic Effects of Extinction in Rats

Abstract: Poor response and high relapse rates remain problematic in the treatment of stress-related psychiatric disorders such as depression and post-traumatic stress disorder. Although mechanisms of pharmacotherapies are intensely studied, little is known about mechanisms of behavioral therapy that could inform improved treatments. We have previously demonstrated the therapeutic effects of extinction learning as a behavioral intervention modeling exposure therapy in rats. In the present study, we tested the hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 65 publications
4
28
1
Order By: Relevance
“…However, several convergent animal studies addressing sex differences in the response to stress have indicated that females can show more resilience than males to the same chronic stress procedures, including those that cause PFC dysfunction (Luine et al, 2007;Wei et al, 2014). In the present study, a modified 21-d CUS paradigm, but not 14-d CUS, impaired performance in the mPFC-mediated set-shifting task in females comparably to the stress-induced set-shifting deficits reported in male rats after 14-d CUS (Bondi et al, 2008;Jett et al, 2017;Fucich et al, 2018). It is possible that removing social defeat stress from the female stress protocol contributed to the need for longer CUS treatment to reach the same behavioral deficit, as social defeat is one of the more robust stress procedures in the CUS protocol.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…However, several convergent animal studies addressing sex differences in the response to stress have indicated that females can show more resilience than males to the same chronic stress procedures, including those that cause PFC dysfunction (Luine et al, 2007;Wei et al, 2014). In the present study, a modified 21-d CUS paradigm, but not 14-d CUS, impaired performance in the mPFC-mediated set-shifting task in females comparably to the stress-induced set-shifting deficits reported in male rats after 14-d CUS (Bondi et al, 2008;Jett et al, 2017;Fucich et al, 2018). It is possible that removing social defeat stress from the female stress protocol contributed to the need for longer CUS treatment to reach the same behavioral deficit, as social defeat is one of the more robust stress procedures in the CUS protocol.…”
Section: Discussioncontrasting
confidence: 45%
“…Notably, mPFC activity is normalized in patients that receive effective behavioral therapy (Yoshimura et al, 2014). Congruently, preclinical studies have demonstrated that chronic unpredictable stress (CUS) impaired cognitive flexibility and attenuated electrical responses evoked in the mPFC by stimulating the excitatory afferent from the mediodorsal thalamus (MDT; Bondi et al, 2008;Fucich et al, 2018). Further, a rat model of behavioral therapy by extinction training effectively restored the afferent-evoked mPFC response and reversed the cognitive set-shifting deficit in stressed rats (Fucich et al, 2016(Fucich et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Originally described by Pinel and Treit in 1978, we have adopted the shock-probe defensive burying test in our lab to model central components of stress-related psychiatric illness, i.e ., preference for passive, avoidant coping strategies versus adaptive, active coping strategies. Using the protocol described here, we have shown that chronic unpredictable stress induces a shift from active to passive coping in adult Sprague-Dawley rats in this test (Jett et al ., 2015; Hatherall et al ., 2017; Fucich et al ., 2016 and 2018), modeling the maladaptive, avoidant coping strategies adopted by patients across many stress-related psychiatric illnesses (Koolhaas et al ., 1999; Bondi et al ., 2007). We have previously described the validity of this test as a measure of anxiety-like responding (see Lapiz-Bluhm et al ., 2008), and have more recently shown the efficacy of novel antidepressant drugs as well as behavioral therapy in reversing chronic stress-induced shifts in coping style choice (Jett et al ., 2015; Hatherall et al ., 2017; Fucich et al ., 2016 and 2018).…”
Section: [Background]mentioning
confidence: 99%
“…Unpublished findings from our lab suggest that surgical disruption of medial prefrontal cortex with chronic cannula implants can abolish burying behavior. Thus, when we have tested the role of this brain region in defensive burying, we have used angled approaches to target the medial prefrontal cortex while minimizing tissue damage to this region with our implants (see Fucich et al ., 2016 and 2018). …”
mentioning
confidence: 98%
See 1 more Smart Citation